Bahasa Inggris dalam Meningkatkan Kompetensi Peserta Didik (Studi kasus di SMA Laboratorium School UPI Bandung) - Sauri, Supyan; Gustania, Ristia; Nugraha, Cepi; Zajuli, Cecep Mustofa (Jurnal Ilmiah Global Education, 2024)
Human is born without any knowledge, besides surely Allah SWT who has given knowledge to the humankind, the parents and the environment around them which are important roles in supplying knowledge to the human who has just known outer world. Human is born and grown and raised need all knowledge. This research aims to monitor the increase in the use of English in learning in the independent learning curriculum at SMA Laboratory School UPI Bandung. The research method used is qualitative with a case study approach, where the researcher asks questions to the Principal, English Teacher and students in the form of a questionnaire and direct interviews. The answers to these questions are arranged in narrative form. The result is an improvement in teacher performance which requires a continuous process of increasing competence that is adapted to the nature of nature and the nature of the times. School principal is also expected to be able to improve teacher performance by carrying out coaching, training, or similar activities to implement learning that supports students. Students also hope that they want to improve their competence in English lessons from all aspects, namely writing, listening, speaking and comprehension.